K‐line X‐ray fluorescence from highly charged iron ions under dense astrophysical plasma conditions. (22nd April 2019) - Deprince, Jérôme; Bautista, Manuel; Fritzsche, Stephan; García, Javier; Kallman, Timothy; Mendoza, Claudio; Palmeri, Patrick; Quinet, Pascal
Abstract : In the present work, we report an investigation of plasma environment effects on the atomic parameters associated with the K‐vacancy states in highly charged iron ions within the astrophysical context of accretion disks around black holes. More particularly, the sensitivity of K‐line X‐ray fluorescence parameters (wavelengths, radiative transition probabilities, and Auger rates) in Fe XVII–Fe XXV ions has been estimated for plasma conditions characterized by an electron temperature ranging from 10 5 to 10 7 K and an electron density ranging from 10 18 to 10 22 cm −3 . In order to do this, relativistic multiconfiguration Dirac‐Fock atomic structure calculations have been carried out by considering a time averaged Debye‐Hückel potential for both the electron–nucleus and electron–electron interactions.